2007
DOI: 10.1097/01.pcc.0000288672.77782.d4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial depression in dengue hemorrhagic fever: Prevalence and clinical description*

Abstract: Transient myocardial depression is not uncommon in patients with DSS. Cardiac dysfunction in children with DSS may contribute to the clinical severity and the degree of fluid overload in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 19 publications
2
44
1
2
Order By: Relevance
“…Myocardial dysfunction was associated with respiratory distress but not with recurrent shock, suggesting the myocardial impairment was sufficient to play a role in fluid overload, following resuscitation and the associated respiratory compromise but not to contribute to the shock syndrome, which appears to be driven predominantly by intravascular volume depletion. These findings are comparable to other echo studies, including one study of Thai children which demonstrated 36% of patients with DSS had reduced systolic function and patients with cardiac impairment were more likely to have fluid overload [18]. The mechanisms underlying this transient myocardial dysfunction in dengue patients remain to be defined, but potential mechanisms may involve some or a combination of the following; myocardial depressant factors, myocardial interstitial oedema, abnormal coronary microcirculation and endothelial dysfunction and also abnormal calcium homeostasis [8, 19, 20].…”
Section: Discussionsupporting
confidence: 87%
“…Myocardial dysfunction was associated with respiratory distress but not with recurrent shock, suggesting the myocardial impairment was sufficient to play a role in fluid overload, following resuscitation and the associated respiratory compromise but not to contribute to the shock syndrome, which appears to be driven predominantly by intravascular volume depletion. These findings are comparable to other echo studies, including one study of Thai children which demonstrated 36% of patients with DSS had reduced systolic function and patients with cardiac impairment were more likely to have fluid overload [18]. The mechanisms underlying this transient myocardial dysfunction in dengue patients remain to be defined, but potential mechanisms may involve some or a combination of the following; myocardial depressant factors, myocardial interstitial oedema, abnormal coronary microcirculation and endothelial dysfunction and also abnormal calcium homeostasis [8, 19, 20].…”
Section: Discussionsupporting
confidence: 87%
“…A series of 91 children with dengue hemorrhagic fever or dengue shock syndrome found no patients with troponin T elevation, despite demonstrating that 36% of victims had significant acute reductions in LVEF over the course of the illness (180). Troponin T levels were not statistically different between Plasmodium falciparum-infected patients with uncomplicated malaria and those with clinical cardiac involvement (181).…”
Section: Infection and Myocarditismentioning
confidence: 97%
“…It has been demonstrated that patients with DSS are more prone to myocardial depression with reduction of the left and/or right ventricular function. One study performed in Thailand involving 99 paediatric patients revealed that approximately onethird (9/25) of DSS patients had a ventricular ejection fraction less than 50 % at the critical stage [23]. On the other hand, myocarditis can be completely asymptomatic, as shown by a study conducted in Sri Lanka, revealing 24 % (44/85) of dengue patients with echocardiographic evidence of myocarditis, without any cardiac complaints and with complete resolution during convalescence [3].…”
Section: Casementioning
confidence: 99%